Exploring and practicing trans-cultural humanistic education for medical students based on life education - Yang, Jinfeng; Zhou, Junhai; Pan, Yanhong; Liu, Chen; Deng, Honglin; Chen, Jian (Frontiers in Education, 2025)
Medical humanities are the soul of health education. Humanistic education proposes to improve the conscious and practical activities of educated people and promote their humanity, realize personal and social values, cultivate ideal personalities, and develop a trans-cultural humanistic spirit. The development of higher education has considerably strengthened the integration of scientific and humanistic education in China. This study analyzed the up-to-date teaching situation of medical humanities courses in medical schools considering the following aspects: teachers’ team construction, teaching mode, practical teaching, assessment and evaluation systems, and inadequate platforms. Relevant reforms based on life education were proposed, including improving the integrity of the teaching team, building suitable curriculum system and teaching theory, setting proper evaluation standard for both students and teachers, and providing adequate platforms for practice of humanistic medicine. This study aimed to promote the students’ medical humanities literacy, thus providing potential strategy and reference for improving medical humanistic education.